2021
DOI: 10.3389/fpsyg.2021.636153
|View full text |Cite
|
Sign up to set email alerts
|

HIIT Models in Addition to Training Load and Heart Rate Variability Are Related With Physiological and Performance Adaptations After 10-Weeks of Training in Young Futsal Players

Abstract: IntroductionThe present study aimed to investigate the effects of two high-intensity interval training (HIIT) shuttle-run-based models, over 10 weeks on aerobic, anaerobic, and neuromuscular parameters, and the association of the training load and heart rate variability (HRV) with the change in the measures in young futsal players.MethodsEleven young male futsal players (age: 18.5 ± 1.1 years; body mass: 70.5 ± 5.7 kg) participated in this study. This pre-post study design was performed during a typical 10 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
(132 reference statements)
2
9
0
1
Order By: Relevance
“…This might be interesting since in a futsal match, most efforts last between 1 and 30 seconds with pause intervals ranging from 1 to 15 seconds. [35] These results are similar to those presented in the study by Campos et al [36] in which a HIIT protocol based on a series of sprints was carried out for 10 weeks and obtained improvements in the ability to repeat sprints in young futsal players. However, in these studies NC exercise was not added, whose combination with HIIT has shown a 2.84% improvement in intermittent work performance in our study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This might be interesting since in a futsal match, most efforts last between 1 and 30 seconds with pause intervals ranging from 1 to 15 seconds. [35] These results are similar to those presented in the study by Campos et al [36] in which a HIIT protocol based on a series of sprints was carried out for 10 weeks and obtained improvements in the ability to repeat sprints in young futsal players. However, in these studies NC exercise was not added, whose combination with HIIT has shown a 2.84% improvement in intermittent work performance in our study.…”
Section: Discussionsupporting
confidence: 85%
“…Regarding vertical jumps, the interventions were not enough to yield significant changes. The main reason may be the short duration of the intervention since previous studies on the isolated application of HIIT [36] and NC exercise [37] for 10 weeks did show significant changes in futsal and soccer players. The effects of NC exercise are promising as it is known to target the hamstrings and improve lower limb strength and power, [12][13][14][15] which are important factors for vertical jump performance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the average height in both groups was within the normal population in Indonesia (Riskesdas, 2018). Although PELATDA athletes' height was higher than non-PELATDA athletes', this research results differed from the results of research conducted in Brazil and Spain, which showed that the average height of semi-professional athletes from these two countries was on average 174 cm (Campos et al, 2021;Romero et al, 2020;Sekulic et al, 2020). However, in futsal, no research concluded the correlation between height and performance in the field.…”
Section: Discussionmentioning
confidence: 60%
“…Given that our supramaximal training involved execution of several shuttle-runs, the possibility that this increased time spent accelerating may have contributed to the lower decrease of 10-m sprint speed observed in the EG should not be disregarded. For instance, intermittent shuttle-run training models (due to their directional changes) have been considered effective strategies to maintain or enhance the speed-power-related abilities in team sport players ( Campos et al, 2021 ; Teixeira et al, 2018 ). Another reason for the decrease in 10-m sprint speed following the intervention period could be related to the high-volume of technical-tactical drills (i.e., high endurance demand) and their potential concurrent effects on sprinting ability during a short-term period of the preseason phase, which is also featured by high training loads and accumulated fatigue ( Nakamura et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%